Vertebral Hemangioma Mimicking Bone Metastasis in 68Ga—PSMA Ligand PET/CT. (May 2017) - Artigas, Carlos; Otte, François-Xavier; Lemort, Marc; van Velthoven, Roland; Flamen, Patrick
Abstract : Abstract: 68 Ga-PSMA PET/CT was performed in a 68-year-old man to evaluate recurrent prostate cancer due to elevated serum prostate-specific antigen level. Images showed a focal uptake in the prostatic gland, suggesting local relapse, and an intense uptake in the 12th thoracic vertebra, with no morphological abnormalities in CT slices. In order to confirm extraprostatic disease and before radiotherapy planning, a full-spine MRI was performed, resulting with the morphological pattern of a vertebral hemangioma. Hystological analysis confirmed the local relapse in the prostate. No radiotherapy treatment was given to the vertebra, and after 1 year of follow-up without systemic treatment, prostate-specific antigen is still undetectable.